Chitosan-titanium nanoparticle coated papers for active packaging - ÖZCAN, ARİF; ARMAN KANDIRMAZ, EMİNE (My University, 2023)
In this study, it was aimed to increase the antimicrobial properties by combining chitosan and titanium nanoparticles. First, titanium nanoparticles were synthesized by sol-gel method and nanoparticles were modified with thiol groups. The chitosan has been modified with allyl glycidyl ether. Both obtained molecules were linked to each other by a thiol-ene click reaction. The chemical structure of the obtained chitosan modified titanium nanoparticles was elucidated by ATR-FTIR. Paper coating formulations were prepared by using the produced nanoparticles and hydroxy ethyl cellulose at different rates and applied on the base paper. Color, gloss, surface energy, contact angle, air permeability properties of the papers were determined by spectrophotometer, glossmeter, goniometer and L&W air permeability device, respectively. Screen prints were made on coated papers and their printability properties were examined. Antimicrobial properties of titanium nanoparticles, chitosan and chitosan modified titanium nanoparticles were determined against E. coli and S. aureus by disk diffusion method. As a result, it has been determined that both titanium and chitosan have antimicrobial properties against both bacterial species separately and the produced chitosan modified titanium nanoparticles increase this antimicrobial property more having a synergetic effect. It has been concluded that the produced antimicrobial papers have a high upside to be active packaging printing material.
Keywords: Tarımsal Bilimler; Ziraat; Gıda Mühendisliği; Mühendislik ve Teknoloji; Agricultural Sciences; Agriculture; Food Engineering; Engineering and Technology; Tarım ve Çevre Bilimleri (AGE); Tarım Bilimleri; GIDA BİLİMİ VE TEKNOLOJİSİ; Agriculture & Environment Sciences (AGE); AGRICULTURAL SCIENCES; FOOD SCIENCE & TECHNOLOGY; Yemek bilimi; Yaşam Bilimleri; Food Science; Life Sciences; Active packaging; Antimicrobial; Printability; Thiol-ene click; Titanium nanoparticle